2002
DOI: 10.1191/1352458502ms835oa
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis functional composite: impact of reference population and interpretation of changes

Abstract: The Multiple sclerosis functional composite (MSFC) has been recommended as a clinical outcome measure to be used in future MS trials. A specific characteristic of the MSFC is that it is defined as a measure of impairment relative to a reference population. Using different reference populations affects actual MSFC scores. If the selection of a reference population also has an effect on sensitivity to change of the MSFC, comparison of data from clinical trials will be almost impossible when different reference p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
0
24
0
2
Order By: Relevance
“…The wide variation in MSFC changes over different studies is probably related to differences in the type and length of the intervention. On the other hand, it has been shown that the use of different reference populations has an effect on Zscores and, consequently, on MSFC scores [37]. Like Cohen et al [5], we applied an internal reference population where the means and standard deviations of the None of the differences between groups were significant either at baseline (p > 0.1) or at 6 months (p > 0.2) Table 3 MSQOL-54 scale scores (mean ± SD) of the two study groups and magnitude of change (effect size) in each scale baseline measurements for all study patients were used.…”
Section: Discussionmentioning
confidence: 98%
“…The wide variation in MSFC changes over different studies is probably related to differences in the type and length of the intervention. On the other hand, it has been shown that the use of different reference populations has an effect on Zscores and, consequently, on MSFC scores [37]. Like Cohen et al [5], we applied an internal reference population where the means and standard deviations of the None of the differences between groups were significant either at baseline (p > 0.1) or at 6 months (p > 0.2) Table 3 MSQOL-54 scale scores (mean ± SD) of the two study groups and magnitude of change (effect size) in each scale baseline measurements for all study patients were used.…”
Section: Discussionmentioning
confidence: 98%
“…Nossos resultados demonstraram que no 25-F W o escore dos homens é significantemente maior se comparado com as mulheres, resultados estes semelhantes aos encontrados na população alemã 17 .…”
Section: Discussionunclassified
“…Com relação ao PA S AT, não observamos diferenças significantes no teste de 3 segundos, porém no teste de 2 segundos observamos melhor desempenho dos indivíduos de sexo masculino e naqueles com maior escolaridade, embora autores atribuam a correlação deste teste ao QI dos pacientes 21 é bem demonstrada a interferência da escolaridade no desempenho final 17 .…”
Section: Discussionunclassified
“…20 Impaired dexterity was defined as an abnormal score (mean -1.96 SD, healthy Dutch reference population) for the 9-Hole Peg Test. 21 Cognitive impairments were defined as a score of mean -SD for 1 or more subtests of a cognitive screening test that was specifically developed for MS, which includes the subscales Consistent Long Term Retrieval and Long Term Storage of the Selective Reminding Test measuring verbal learning and memory, the 10/36 Spatial Recall Test measuring visuospatial learning and delayed recall, the Symbol Digit Modalities Test measuring sustained attention and concentration, the Paced Auditory Serial Addition Test measuring sustained attention and information processing speed, and the Word List Generation measuring verbal fluency. [22][23][24] Incontinence was defined as a score of 5 or lower for the continence item of the FIM.…”
Section: Discussionmentioning
confidence: 99%